Rancang Bangun Sistem Informasi Pencatatan Bulan Imunisasi Anak Sekolah dengan Metode Waterfall - Fiqar, Tegar Palyus (Journal Geuthee of Engineering and Energy, 2022)
The Health Service has main task to assist the Governor in carrying out mandatory authority of the Government in the field of health submitted to the Regional Government in accordance with Government Regulation No. 38/2007. In Government Regulation No. 7/2007, City Health Office must carry out deconcentration and co-administration tasks in health section that have been delegated by the Governor in accordance with tasks related to the health sector. In carrying out these tasks, the Health Servicehas several functions, one of which is to provide guidance, service, supervision, control, monitoring, evaluation and reporting of health management. From this function, the Health Service has authority in supply and management of drug stocks, medical tools and vaccines. In process of supply and management, there are several obstacles experienced by the City Health Office, including immunization data, stock of drugs, vaccines and medical devices that have no system-based bookkeeping. So the process of recording and reporting experiencing difficulties including data that must be searched manually and high risk of data loss or damage. Therefore, in this study the development of a recording and reporting  system in the Balikpapan City Health Office aims to assist the process of recording and reporting so that the process of providing and managing is easy and minimizing the occurrence of errors. The Information System for Recording and Reporting of School Children Immunization Months was developed using the Code Igniter framework with the concept of Model, View and Controller (MVC) architecture. Development of Information System for Recording and Reporting the Month of Immunization for School Children using a MySQL database.  The method used is the waterfall method. The steps taken are requirements, design, implementation, verification, and maintenance. The results obtained from this study are information systems for recording and reporting months of immunization of school children.